How Women Participate in Regional Elections as Candidates After North Maluku Became New Province? - Abd. Rasyid, Syamsul Bahri (LPPM Universitas Jambi, 2024)
In the 2020 regional elections, North Maluku had a female regional head for the first time, namely in the Sula Islands Regency. This research seeks to explore the involvement of women as contestants in the regional elections in North Maluku as regional head candidates. Qualitative research methods were used in this research with a case study approach. Data was collected by documentation, namely by looking at the distribution of news reports by local media and supported by other documents such as documents from the KPU and the Constitutional Court. The data set was analyzed using NVivo 12 plus, to see the dominant tendencies and to draw conclusions. The research results show that North Maluku has only had four women run as regional head candidates after being expanded in 1999 and then implementing direct regional elections for the first time in 2005 until the 2020 regional elections. The three main factors behind these candidates' participation are kinship politics, political experience, and political dynasty. Of the four candidates, only Fifian could emerge as elected regional head, and Fifian could utilize his accumulated capital to convert it into victory. The accumulation of modalities, such as social capital, political capital, economic capital, cultural capital, and symbolic capital, mostly comes from the base of the political dynasty built by the Mus family.